Aproximación a un instrumento de diagnóstico sobre la visibilidad: el caso de las profesoras universitarias - Castro Ceacero, Diego (2012)
Approach to a diagnostic instrument about visibility: the case of women professors in university This article discusses the concept and diagnosis of the visibility of women in the contemporary university. Thereafter, we construct a theoretical model that consists of three variables: the participation, expertise and power as manifested in the different functions of academics: teaching, research and management. We propose a tool to determine and diagnose the level of visibility of the teachers at the university. The instrument could be applied to the visibility of other specific groups. The goal is not only possible diagnosis, but also the ability to design actions to improve the visibility of academic college.